Automatic Identification of Lifestyle and Environmental Factors from Social History in Clinical Text - Yetisgen, Meliha; Pellicer, Elena; Crosslin, David; Vanderwende, Lucy (Proceedings of AMIA 2016 Joint Summits on Translational Science, 2016)
Lifestyle and environmental factors play a significant role both in clinical research as well as clinical care. In clinical research, it has been established that 5-10% of cancers can be attributed to hereditary factors, while 90-95% have been found correlated with lifestyle and environmental factors such as smoking, diet and exercise. For clinical care, it has long been practice to record social history during clinical care as this history impacts not only diagnosis but also treatment options. We therefore propose in this work to automatically identify those lifestyle and environmental factors that clinical caregivers have documented. We extended Milton et. al.’s analysis of social and behavior information and Uzuner et. al.’s information on smoking in discharge summaries.